Improving the Operational Stability of PBDTTTz‐4 Polymer Solar Cells Modules by Electrode Modification1. Issue 4 (17th September 2015) - Roth, Bérenger; A. dos Reis Benatto, Gisele; Corazza, Michael; Carlé, Jon E.; Helgesen, Martin; Gevorgyan, Suren A.; Jørgensen, Mikkel; Søndergaard, Roar R.; Krebs, Frederik C.
Abstract : PBDTTTz‐4 is employed in the ambient manufacturing of fully Roll‐to‐Roll organic solar cell modules. Modules are manufactured using a novel silver nanowire electrode or a previously reported carbon electrode. The average PCE of carbon modules (3.07%) and AgNW modules (1.46%) shows that PBDTTTz‐4 is a good candidate for upscaling. Stability measurements following the ISOS standards are used to compare the lifetime of the different modules. In all tests but one, the carbon modules are less stable. The higher stability of AgNW is attributed to the removal of the PEDOT:PSS in the front electrode. Finally during indoor light tests, a new degradation phenomenon is observed where bubbles are formed inside the modules contrary to previous reports of bubble formation by thermal expansion of trapped gas inside the barrier. Abstract : The lifetime of large area organic solar cell modules is studied during both indoor and outdoor tests . The modules are fully roll‐to‐roll manufactured in ambient air with the high‐efficiency polymer PBDTTTz‐4. The stability of modules with various ITO‐free electrodes is compared. During high‐temperature tests, a new type of degradation mechanism is observed.